Outcome of PKM (Community Service Program) on Promoting Vegetable Consumption as a Strategy for Addressing Stunting Risk Groups in Coastal Areas. - Rumbya, Lisri; Salakory, Melianus (GEOFORUM, 2024)
Indonesia is facing a severe issue of child malnutrition with high rates of stunting among toddlers, particularly in coastal areas like Pulau Osi Maluku. Stunting is caused by inadequate nutritional intake over a long period. The prevalence of stunting in Indonesia remains high, although it is decreasing. Preventive efforts include promoting the habit of eating vegetables, providing health education to parents, and developing hydroponics as a solution for vegetable supply in areas with limited land. Education and collaboration between the government and the community are crucial in addressing stunting and improving the quality of life for children in coastal areas. The research was conducted in Pulau Osi Hamlet, Maluku, using purposive sampling with mothers as subjects. A descriptive qualitative approach was employed, utilizing both primary and secondary data. Data collection was carried out through interviews, observations, and documentation. Data analysis was done using qualitative methods to describe the research findings systematically. In Pulau Osi Hamlet, efforts to combat stunting and meet vegetable needs were undertaken through education using the PBL (Problem-Based Learning) method, involving 35 participants. Vegetable consumption patterns varied and were influenced by knowledge, education, and the availability of vegetables. Land and supply limitations posed challenges. The hydroponic solution increased vegetable availability, diversified food options, and promoted community self-sufficiency. Collaboration between the government and the community was vital. The results were evident from the healthy growth of vegetable plants and successful harvests. This initiative successfully improved knowledge, self-sufficiency, and food security in Pulau Osi Hamlet, helping to address stunting and improve vegetable consumption patterns.